The Transcription Factor Hif-1 Enhances the Radio-Resistance of Mouse MSCs - Calvo-Asensio, Irene; Dillon, Eugène T.; Lowndes, Noel F.; Ceredig, Rhodri (Frontiers in Physiology, 2018)
Mesenchymal stromal cells (MSCs) are multipotent progenitors supporting bone marrow hematopoiesis. MSCs have an efficient DNA damage response (DDR) and are consequently relatively radio-resistant cells. Therefore, MSCs are key to hematopoietic reconstitution following total body irradiation (TBI) and bone marrow transplantation (BMT). The bone marrow niche is hypoxic and via the heterodimeric transcription factor Hypoxia-inducible factor-1 (Hif-1), hypoxia enhances the DDR. Using gene knock-down, we have previously shown that the Hif-1α subunit of Hif is involved in mouse MSC radio-resistance, however its exact mechanism of action remains unknown. In order to dissect the involvement of Hif-1α in the DDR, we used CRISPR/Cas9 technology to generate a stable mutant of the mouse MSC cell line MS5 lacking Hif-1α expression. Herein, we show that it is the whole Hif-1 transcription factor, and not only the Hif-1α subunit, that modulates the DDR of mouse MSCs. This effect is dependent upon the presence of a Hif-1α protein capable of binding to both DNA and its heterodimeric partner Arnt (Hif-1β). Detailed transcriptomic and proteomic analysis of Hif1a KO MS5 cells leads us to conclude that Hif-1α may be acting indirectly on the DNA repair process. These findings have important implications for the modulation of MSC radio-resistance in the context of BMT and cancer.